Model of Start Up Management to Strengthen Student Entrepreneurship Program in The MERDEKA Campus - Ida Hindarsah; Yuce Sariningsih; Yusep Ikrawan; Heri Erlangga; Erik; Andry Mochamad Ramdan (PT Mattawang Mediatama Solution, 2023)
The government's seriousness towards the growth and development of entrepreneurship is felt by universities. One of them is the birth of the Free Learning and Independent Campus (MBKM) program. The Merdeka Campus programs aim to prepare students to become graduates who have the competencies needed in the future and as respond to digital transformation that is happening globally has pushed Indonesia to become a country that excels in giving first to start-up. The research purposes to investigate the implementation of start-up management to strengthen student entrepreneurship program. This research will be conducted at Pasundan University. The method used is the Mix Method approach, namely a quantitative approach (survey) supplemented by qualitative data (interviews and Focus Group Discussions). The survey was conducted to 54 active student respondents at the University, as well as Focus Group Discussions. The results showed that the effect of creativity and innovation on motivation was 42,5% and motivation on management was 33,9%. Due to the small management influence, tools are needed to help improve start-up capabilities in increasing profits, market size and productivity through online interactions with business websites.